Multivariate GARCH models - Annastiina Silvennoinen; Timo Teräsvirta (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
This article contains a review of multivariate GARCH models. Most common GARCH models are presented and their properties considered. This also includes semiparametric and nonparametric GARCH models. Existing specification and misspecification tests are discussed. Finally, there is an empirical example in which several multivariate GARCH models are fitted to the same data set and the results compared with each other.
Keywords: C32; C52; 330; autoregressive conditional heteroskedasticity; modelling volatility; nonlinear GARCH; nonparametric GARCH; semiparametric GARCH; Mathematik; ARCH-Modell